A probabilistic simplified Seismic Model from Ambient Vibrations (SMAV) of existing reinforced concrete buildings. (1st July 2021) - Spina, D.; Acunzo, G.; Fiorini, N.; Mori, F.; Dolce, M.
Highlights: The structural behaviour of the infilled RC buildings is analysed. A probabilistic model is proposed for structural seismic response of RC buildings. Frequencies from ambient vibrations are used for a simplified structural model. Relationships between frequency variation and structural deformation are given. Seismic experimental data of monitored buildings are used to validate the model. Abstract: SMAV (Seismic Model from Ambient Vibrations) is a mathematical model for predicting the seismic response of an existing building subjected to earthquake that produces no severe damage. The model is based on the identification of the building experimental modal parameters from ambient vibration together with few information about its geometry and constructive typology. The dynamic response of the structure is obtained by a modal superposition where all the inertial properties are concentrated in the center of gravity of the floors or floor sections. The non-linear behavior, which typically occurs during even nondestructive earthquakes, is considered by assigning appropriate laws of variation to the natural frequencies as the deformation increases. This paper presents the development of SMAV to reinforced concrete frame buildings with infill walls and the application to real cases. Specific Frequency Shift Curves (FSCs), that relates the vibration amplitude to the variations of the natural frequencies, have been developed. Such FSCs are a fundamental feature of SMAV, because they allow the seismic nonlinear behavior to be simulated through an equivalent iterative linear analysis. Therefore, in order to comply with the declared aim, in this work the attention is focused on the definition of a suitable simplified model for the generation of FSCs, valid for reinforced concrete frame buildings with infill walls. In the adopted model the global behavior of the infilled frame is simulated by considering the two components of the system, i.e the bare frame and the infill masonry panel, as working in parallel. The mutual interaction between them is modeled by suitably modifying the collapsing mechanism of the masonry panel. The stochastic approach for modeling the seismic response of infilled RC buildings, considering different kinds of infills and taking account of the nonlinearity which arises during a seismic event, is illustrated in detail. The validation of the FSCs has been performed by using the experimental seismic response of buildings as recorded by permanent accelerometric monitoring systems. Finally, two case studies related to the seismic response recorded on a regular and an irregular building, respectively, are presented by comparing the computed end experimental seismic dynamic responses, in order to prove the SMAV ability in reproducing the behavior of RC infilled frame buildings subjected to nondestructive earthquakes.